The influence of OATP2B1 and atorvastatin on coproporphyrin isomers in rats - Kinzi, Jonny; Grube, Markus; Hussner, Janine; Seibert, Isabell; Hamburger, Matthias; Meyer zu Schwabedissen, Henriette E. (Journal of pharmacological sciences, 2023)
Coproporphyrin I (CPI) and III (CPIII) are discussed as biomarkers for organic anion transporting polypeptides (OATPs). We report on CPI and CPIII levels in wildtype, rSlco2b1-knockout, and SLCO2B1-humanized rats at baseline and after administration of atorvastatin, an inhibitor of the CPIII-specific rOATP2B1/hOATP2B1 and the CPI/CPIII-transporting rOATP1B2. OATP-inhibition by atorvastatin leads to significantly increased CPI and CPIII serum levels. However, basal CP serum levels in rSlco2b1-knockout animals were significantly lower (CPI), or unaffected (CPIII). In the presence of atorvastatin, this genotype effect was abolished. In conclusion, our results indicate an unexpected impact of OATP2B1 on CP serum levels in rats.